Right ventricular function assessed by cardiac magnetic resonance predicts the response to resynchronization therapy. Issue 4 (April 2020) - Manca, Paolo; Cossa, Stefano; Matta, Gildo; Scalone, Antonio; Tola, Gianfranco; Schintu, Barbara; Setzu, Agostino; Melis, Marco; Giardina, Achille; Corda, Marco; Sinagra, Gianfranco; Porcu, Maurizio
Abstract : Background and aim: Cardiac resynchronization therapy (CRT) reduces mortality and morbidity in chronic heart failure symptomatic patients with broad QRS who are already undergoing optimal medical treatment. However, approximately one-third of implanted patients do not show any benefit from this treatment. Right ventricle (RV) dysfunction leads to a worse outcome in patients with heart failure, but its role in predicting the response to CRT has shown conflicting results. The purpose of our study was to investigate how the RV function, assessed by cardiac magnetic resonance (CMR), could influence the outcome of heart failure patients treated with CRT. Methods and results: We retrospectively enrolled 72 heart failure patients, 38 affected by dilated cardiomyopathy (DCM) and 34 by ischemic dysfunction, with left bundle branch block, QRS greater than 120 ms and standard indications to CRT. We defined the response to CRT as an improvement of at least 10% of the left ventricular ejection fraction (LVEF) or at least one of the NYHA functional classes. We stratified the population into two groups based on the right ventricle ejection fraction (RVEF) at CMR: group 1 RVEF at least 55% ( n  = 32), group 2 RVEF less than 55% ( n  = 40). After a mean follow-up of 38 ± 12 months, 44 patients (61%) were considered responders whereas 28 (39%) did not show any benefit. Patients in group 1 had a higher rate of response to CRT (75 vs. 50%, P  = 0.03). At the univariate analysis RVEF [54 vs. 43%; confidence interval (CI) = 0.907–0.980; hazard ratio = 0.943; P  = 0.003], RV end-systolic volume (56 vs. 84 ml; CI = 1.005–1.034; hazard ratio = 1.019; P  = 0.008) and tricuspid annular plane systolic excursion (TAPSE) (16.4 vs. 14 mm; CI 0.745–0.976; heart rate = 0.853; P  = 0.021) were the parameters most strongly associated with the response to CRT. Male sex, atrial fibrillation, and older age also negatively influenced the outcome. At a multivariate model, RVEF and older age remained significant. Conclusion: In our experience, patients with RV dysfunction less likely benefited from CRT. RV assessment, studied with CMR, appears to be a good predictor of the response to biventricular stimulation.